2020
DOI: 10.1002/art.41425
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies in Critically Ill Patients With COVID‐19

Abstract: Objective Coagulopathy is one of the characteristics observed in critically ill patients with coronavirus disease 2019 (COVID‐19). Antiphospholipid antibodies (aPLs) contribute to coagulopathy, though their role in COVID‐19 remains unclear. This study was undertaken to determine the prevalence and characteristics of aPLs in patients with COVID‐19. Methods Sera collected from 66 COVID‐19 patients who were critically ill and 13 COVID‐19 patients who were not critically ill were tested by chemiluminescence immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
189
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(202 citation statements)
references
References 18 publications
4
189
1
8
Order By: Relevance
“…Nevertheless, the pathogenicity of APL from COVID-19 patients was proven elegantly in a pre-publication by Zuo et al, in which IgG aPS/PT antibodies led to NETosis in vitro , thus contributing to thrombus formation, and increased thrombus extension in vivo in a mouse model ( 104 ). This finding is corroborated by the observation that APL occur preferably in critically ill patients ( 103 ). Altogether, the risk of thrombosis mediated by APS should be kept in mind and a prolonged aPTT should not prevent proper anticoagulation in patients.…”
Section: Rheumatic Diseases and Covid-19supporting
confidence: 69%
“…Nevertheless, the pathogenicity of APL from COVID-19 patients was proven elegantly in a pre-publication by Zuo et al, in which IgG aPS/PT antibodies led to NETosis in vitro , thus contributing to thrombus formation, and increased thrombus extension in vivo in a mouse model ( 104 ). This finding is corroborated by the observation that APL occur preferably in critically ill patients ( 103 ). Altogether, the risk of thrombosis mediated by APS should be kept in mind and a prolonged aPTT should not prevent proper anticoagulation in patients.…”
Section: Rheumatic Diseases and Covid-19supporting
confidence: 69%
“…Interestingly, IgG/IgM anti-prothrombin and IgG/IgM anti-annexin-V data show that distribution of positive cases number increases in late infection patients, signi cantly in anti-annexin-V results, suggesting a possible role for these anti-phospholipids antibodies in disease course. In fact, it has been reported that aPLs can arise transiently in some patients with critical illness and SARS-CoV-2 infection (disappearing in a few weeks) [22]; as well as in other genetically predisposed patients they could trigger a "COVID-19-induced-APS-like-syndrome" or other autoimmune diseases [27][28]. Unfortunately, we could not perform a longer-term follow up.…”
Section: Resultsmentioning
confidence: 90%
“…Finally, despite IgA aCL and IgA aβ2GP1 are not included in the current APS classi cation criteria [30], recent evidences highlight a possible role for IgA anti-phospholipids antibodies in genetically predisposed patients [27]. Being IgA antibodies the most important immunoglobulins to counteract infectious pathogens in respiratory and digestive systems, they have an important role in mucosal immunity.…”
Section: Resultsmentioning
confidence: 99%
“…90 A study from a Wuhan hospital found that, of the 66 patients who were critically ill due to Covid19, 47% had positive antiphospholipid antibodies and that patients who had more than one, where the value of at least one was >40 CU, had an increased risk of cerebral infarction (p 0.023). 91 Other cases are reported of pulmonary emboli, ischaemic strokes, limb and digital ischaemia and deep vein thromboses in patients with positive antiphospholipid antibodies. 85,[92][93][94][95] A French study of 150 patients on an intensive care unit due to COVID-19 related ARDS found that 64/150 had clinically significant thrombotic events during ICU stay.…”
Section: Anti-phospholipid Syndrome and Covid-19mentioning
confidence: 99%